RESISTANCE AND SENSITIVITY PATTERN OF STAPHYLOCOCCUS AUREUS; A STUDY IN LADY READING HOSPITAL PESHAWAR (Retracted) - Naeem, Mohammad; Adil, Muhammad; Naz, Syeda Maria; Abbas, Syed Hussain; Khan, Muhammad Zia ul Islam; Khan, Ayasha; Khan, Muhammad Usman (Journal of Postgraduate Medical Institute, 2012)
Objective This study was done to determine the sensitivity and resistance pattern to the most commonantibiotics in use. Methodology The data for this retrospective study was obtained and analysed from October 2010 toOctober 2011 in Lady Reading Hospital, Peshawar. Purposive sampling and univariate analysis was done.2058 samples were cultured for sensitivity using Kirby Bauer's Diffusion technique and in a period of oneyear, growth of Staphylococcus aureus was obtained in 723 samples. These 723 growths were obtainedfrom clinical isolates of pus (699), blood (16) and urine (8). Fourteen drugs from five different classes ofantibiotics were tested for sensitivity against Staphylococcus aureus. Results Most of the growth was obtained from pus (96.7%). Resistance was high to all groups ofantibiotics except glycopeptides. There was no case of Vancomycin Resistant Staphylococcus aureus(VRSA). Out of 723 samples, 228 (31.5%) were Methicillin Resistant Staphylococcus aureus (MRSA). Theresistance to a representative antibiotic of each group is as follows: Ciprofloxacin (Fluoroquinolone)51.7%, Cephradine (Cephalosporin) 46.2%, Amoxicillin+Clavulanic Acid (Penicillin group) 45.6%,Imipenem+Cilastatin Sodium (Carbapenem) 42.0% and Teicoplanin (Glycopeptide) 19.8%. Conclusion Resistance of Staphylococcus aureus to Teicoplanin and most of the antibiotics is high andstrict guidelines are required to control unnecessary prescriptions and over the counter sale of antibiotics.